Nurse misinformation and the digital era: Abrogating professional responsibility - Charles, Christopher M (Nursing ethics, 2025)
In the current digital era, reliance on technology for communication and the gathering and dissemination of information is growing. However, the information disseminated can be misleading or false. Nurses tend to be trusted by the public, but not all information brought to the public forum is well-informed. Ill-informed discussions have resulted in harm to individuals who take such information as fact and act on it. As technology continues to evolve and fact versus fiction becomes more challenging to discern, it is critical that nurses recognize their ethical responsibility to the public in providing information for which sound evidence exists. This analysis will explore medical misinformation through concepts such as confirmation bias and the politicization of science. Also, the impact of nurses not recognizing the power and responsibility associated with using their credentials in public fora, even when the central motivator is that they believe they are helping other individuals. Using nursing goals and perspectives, we will discuss the ethical responsibility of nurses to be aware of the soundness of what they think they know. Utilizing ideas of professional responsibilities, as outlined by professional codes of ethics as well as the ethical principles of non-maleficence and veracity, we explore the problem of nurses propagating misinformation and suggest strategies to enhance nurse awareness of their ethical responsibilities for veracity and transparency regarding what is known and what is not.